Áreas Verdes Urbanas y Salud Pública en México: Resultados de una encuesta en línea en 2021 - Romero Saavedra, Adriana (2022)
Vegetation provides human beings with social, environmental, aesthetic, and health benefits. Some of the health problems are preventable such as hypertension, diabetes and obesity, diseases classified as chronic non-communicable. The Panamerican Health Organization confirms that chronic non-communicable diseases are the leading causes of death and disability in the world (PAHO, 2019). The objective of the research was to describe, through an online survey to a group of 126 Mexicans aged 20 and older from different cities in the country, the characteristics of the UGA urban green areas near their home, their health status, and to describe the associations that were found through a qualitative descriptive analysis of 126 responses. Where 50.8% of those surveyed have not been diagnosed with obesity/overweight, and 40.48% of this group does have UGA near their home, and they usually carry out some activity in the area. So, it can be concluded that those persons who have urban green areas near their home use them, which could suggest that they provoke an invitation to visit them and do physical and relaxation activities, which favors their health, since this group of respondents does not have the most important risk factor that triggers other health problems such as hypertension and diabetes.